Utilização do poliestireno expandido quimicamente modificado como superplastificante no concreto - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Many concrete properties are the result of the amount of water used in the mixture of its components, the superplasticizers have the ability to disperse cement particles and release water trapped between them causing a smaller amount of water is necessary to meet certain consistency. The sulfonated polystyrene has great potential to be used as the superplasticizer due to the ability to be adsorbed onto the cement particles and inducing repulsive forces. This study aimed to evaluate the physical properties of concrete using sulfonated polystyrene as superplasticizer. The influence of sulfonated polystyrene left in the concrete of a reference concrete, which was added different percentages of additive to achieve the standard consistency. Evaluated the percentages were 0.5; 1.0 to 1.5% admixture relative to the cement mass. The sulfonated polystyrene acted as a reducing particle dispersant 1.71% and 8.67% of the amount of water percentage to 0.5% and 1.0% respectively. However, the compressive strength and diametral tensile compression of the cured concrete after 28 days it was reduced as the percentage of polystyrene was increased. The strength loss is caused due to reduction of the specific weight of the concrete. The determining factor for the loss of density and loss of particle dispersibility was pH admixture resulting acid after the chemical reactions. There was no change in water absorption and void index for the percentages of 0.5% and 1.0% additive, only the highest percentage relative to the cement mass obtained a reduction in these parameters.
Keywords: Civil engineering; Admixture; Concrete; Strenght; Engenharia civil; Aditivos; Concreto; Resistência; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL